Therapeutic strategies to recover ependymal barrier after inflammatory damage: relevance for recovering neurogenesis during development - Paez-Gonzalez, Patricia; Lopez-de-San-Sebastian, Javier; Ceron-Funez, Raquel; Jimenez, Antonio J.; Rodríguez-Perez, Luis Manuel (Frontiers in Neuroscience, 2023)
The epithelium covering the surfaces of the cerebral ventricular, is known as the ependyma, and is essential for maintaining the physical and functional integrity of the central nervous system. Additionally, the ependyma plays an essential role in neurogenesis, neuroinflammatory modulation and neurodegenerative diseases. Ependyma barrier is severely affected by perinatal hemorrhages and infections that cross the blood brain barrier. The recovery and regeneration of ependyma after damage are key to stabilizing neuroinflammatory and neurodegenerative processes that are critical during early postnatal ages. Unfortunately, there are no effective therapies to regenerate this tissue in human patients. Here, the role of the ependymal barrier in the context of neurogenesis and homeostasis are reviewed, and future research lines for development of actual therapeutic strategies are discussed.